Childhood peak flow and the Oxford Transport Strategy. Issue 8 (3rd December 2008) - MacNeill, S J; Goddard, F; Pitman, R; Tharme, S; Cullinan, P
Abstract : Background: Studies of the health effects of traffic interventions are rare. The Oxford Transport Strategy (OTS), implemented in June 1999, involved a wide range of permanent changes designed to reduce congestion in the city centre of Oxford, UK. The impact of the OTS on peak expiratory flow (PEF) and respiratory symptoms among schoolchildren in the city is reported. Methods: A dynamic cohort of 1389 children aged 6–10 years attending first schools in Oxford was studied. Schools were visited 2–3 times a year for 5-day periods between 1998 and 2000. On each day of each visit children had their PEF measured and were asked about their respiratory symptoms. Results: Changes in traffic varied across the city. In the whole population, regression analysis of daily PEF adjusting for potential confounders showed statistically significant improvements post-OTS (β = 5.52 l/min, 95% CI 3.08 to 7.97), but there was no consistent evidence that these improvements varied by changes in traffic exposure. In post-hoc analyses, children currently receiving treatment for asthma tended to experience a greater increase in PEF post-OTS as did children from less affluent homes, although these differences did not reach statistical significance. In each of these groups, greater benefits were observed among those living near roads where traffic levels fell post-OTS. Conclusions: These findings suggest that traffic management may lead to small localised improvements in childhood respiratory health and that such benefits are limited to children with pre-existing respiratory problems and those from less affluent backgrounds.